Research advances of histone deacetylases in acute kidney injury - Deng Fang-jing; Zhu Jie-fu; Wu Xiong-fei (Linchuang shenzangbing zazhi)
Histone deacetylases （HDACs） are expressed by silencing the deacetylation of histone lysine.HDACs can also deacetylate non-histone proteins and regulate cell biological functions.Abnormal function of HDACs is closely correlated with the occurrence and development of tumor，neurodegenerative disease，inflammatory reactive disease and kidney disease.This review summarized the latest researches of HDACs in acute kidney injury.